Rola sektora oficjalnego w restrukturyzacji długu państwowego - Mesjasz, Lidia (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The history of sovereign debt restructuring shows that for nearly last two centuries official sector has tried to distance itself from direct responsibility for the recovery of private loans to sovereign debtors, by pushing it onto the judiciary or the multilateral financial institutions, especially the IMF. The latest effort came in 2002 when the management of the IMF proposed a formal Sovereign Debt Restructuring Mechanism that would have established an independent framework for handling future sovereign debt problems along the lines of a transnational bankruptcy code. The SDRM was intended to accomplish what the diplomats, gunboat captains, administrators, and judges of the last two hundred years failed to achieve: an effective method by which the official sector could encourage orderly workouts of private sector claims against distressed sovereigns without shouldering the full moral, political, and financial responsibility for these workouts. For many reasons the SDRM proposal did not prosper. Thus, unable to let go, unwilling to take charge, and historically incapable of striking a happy compromise between the two, the official sector's role in future debt restructurings will remain ad hoc and unpredictable. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1191, s. 304-315